Water-soluble bitumen degradation products can fuel nitrate reduction from non-radioactive bituminized waste. (March 2020) - Mijnendonckx, Kristel; Van Gompel, Axel; Coninx, Ilse; Bleyen, Nele; Leys, Natalie
Abstract: An important fraction of the currently stored volume of long-lived intermediate level radioactive waste in Belgium is immobilized as Eurobitum. This type of waste typically contains large amounts of NaNO3 homogeneously dispersed in a hard bituminous matrix. Geological disposal of Eurobitum in a water-saturated sedimentary formation such as Boom Clay will result in the leaching of high concentrations of NaNO3 in the Boom Clay formation. This could cause a geochemical perturbation of the surrounding clay, possibly affecting some of the favorable characteristics of the host formation such as its hydraulic conductivity, sorption potential or the redox conditions. The latter might result in a decrease of its reducing capacity and an increase in the mobility of redox-sensitive radionuclides. Microbial nitrate reduction is a well-known process, which could be stimulated by the chemical and radiolytical water-soluble organic bitumen degradation products. The present study carried out different series of long-term anoxic batch experiments to investigate the ability of the microbial community of Boom Clay borehole water to reduce nitrate, leaching from thermally aged non-radioactive Eurobitum in the presence or absence of acetate, formate and oxalate, being part of the most important organic bitumen degradation products. Obtained results indicate that all three organic bitumen degradation products can be used as electron donor to fuel microbial nitrate reduction, albeit with a different efficiency. The highest nitrate reduction rate was observed in the presence of acetate, while oxalate was the least efficient electron donor for nitrate reduction. Moreover, organic compounds that leached from the Eurobitum during the course of the experiment were used as electron donor for microbial nitrate reduction in all conditions. Furthermore, calcium oxalate crystals were observed, indicating that if oxalate is present, it will probably be less bioavailable compared to other organic compounds. Highlights: Acetogenesis is the dominant ongoing reaction in synthetic Boom clay porewater. Nitrite temporarily accumulates in most conditions with Eurobitum. Water-soluble bitumen degradation products can fuel microbial nitrate reduction. Phosphate can limit acetate dependent microbial nitrate reduction.